Efektivitas Penggunaan Media Quizizz Terhadap Minat Belajar Siswa Dalam Pembelajaran Online Akuntansi - Indah Cahya Sagala (Journal on Education, 2023)
Accounting is a subject that requires high understanding and concentration to analyze and answer various accounting questions, so it takes a high interest in studying accounting, but due to the emergence of the Covid 19 pandemic, learning activities are carried out online, so media or digital platforms are needed that can arouse students' interest in accounting subjects. This study aims to analyze the effectiveness of using Quizizz media on students' learning interest in accounting online learning. The method used in this study is the systematic literature review method by searching for the keywords "effectiveness" AND "Quizizz" AND "interest in learning" AND "accounting online learning" OR "online learning" in journals published in the last 10 years. The approach used to analyze the data uses planning, conduction, and reporting. The research results of students or students agree that Quizizz is easy to use, exercises with Quizizz are fun, help students review learning material and stimulate their interest in learning accounting. The limitations of this study are related to the limited literature that directly discusses the use of Quizizz media. So, it is hoped that there will be more research on this topic and literature discussing the effectiveness of using Quizizz media in online accounting learning.